U bow activator, an alternative functional orthodontic appliance - Anita Budihardja; Jusuf Sjamsuddin (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Functional orthodontic treatment has been proved to be one of the most effective and successful treatment modality in orthodontics. Functional orthodontic appliance can only be applied in growing young patients. Since Andresen’s activator, there are a lot of other functional appliances that have been developed and introduced. U bow activator, introduced by Prof. Karwetzky from Wilhelms University of Muenster, is one of the appliances that can be chosen. In this case report, U bow activator type 1 is used to treat class II malocclusion and proved to give satisfying result. Patient’s cooperation is the most important factors in achieving success.